Necroptosis has a crucial role in the development of chronic periodontitis - Salehe Akhondian; Kazem Fatemi; Niloofar Ebrahim Zadeh; Seyed Abdolrahim Rezaee; Sahar Bayat; Zahra Shooshtari; Farnaz Mohajertehran (Journal of Oral Biology and Craniofacial Research)
Background and aim: Periodontitis is a non-communicable chronic inflammatory disease that affects the entire periodontium and its severe types cause irreparable destruction. The purpose of this study was to determine the type of cell death in chronic periodontitis (CP) with the expression of receptor-interacting protein kinase (RIPK) type1 and RIPK3 genes. Materials and methods: This cross-sectional study was carried out from September 2019 to 2020. The samples (38 participants) were divided into two groups: 20 recently diagnosed CP patients and 18 healthy individuals. Participants' data was collected in the periodontology Department, Dental school, Mashhad University of Medical Sciences and sent to the Immunology Lab for assessment of RIPK1 and RIPK3 expressions using quantitative real time-PCR. Results: The study sample consisted of 30 females (78.9%) and 8 males (21.1%) with a mean age of 34 ± 5 years. The expression of the genes of interest in CPs exhibited an opposite pattern. Although, RIPK3 gene expression was significantly greater in CP patients compared to the control group (P = 0.024), the expression of RIPK1 decreased (p < 0.001). Moreover, no significant correlation was observed between age and gender with these molecules in CPs. Conclusion: The RIPK3 selectively contributes to necroptosis, therefore, it seems that RIPK3-mediated necroptosis is involved in chronic periodontitis. RIPK1 also participates in necroptosis, but mostly in apoptosis. Therefore, necroptosis as an unprogrammed inflammatory cell death induced by pathogenic damages seems to be another mechanism complicated in periodontitis and could be used as a novel target for CP therapy.